Epistemic uncertainty quantification via uncertainty theory in the reliability evaluation of a system with failure Trigger effect. (November 2021) - Chen, Ying; Li, Shumin; Kang, Rui
Highlights: The epistemic uncertainty of trigger effect in reliability evaluation is analyzed. Uncertain theory is applied to quantify the PoF model-form uncertainty. The uncertain degradation model of failure mechanism is built. Belief reliability of the system with failure trigger effect is deduced. The advantages of the new method are discovered in the engineering case. Abstract: Reliability evaluation of system with dependent failure processes is a problem that draws more research attention. It is essential to quantify the epistemic uncertainty in the system for high evaluation accuracy. Trigger is one of the typical dependent failure processes. Trigger effect indicates that some events occur because of the trigger of other events. This paper studies the epistemic uncertainties in the reliability evaluation of the system with trigger effect based on uncertainty theory. The model-form uncertainty of physics of failure (PoF) model, the failure process uncertainty due to lack of knowledge and the propagation of them in the system are quantified with Belief Adjustment Factors Method (BAFM) and the Liu process. System belief reliability is evaluated by decoupling the correlations between the trigger failure mechanism and triggered failure mechanisms. A conductive slip ring in electromechanical orientation device is introduced as a case. The trigger effect and system belief reliability are analyzed. Results show that, compared with probability method, evaluation values with uncertainty method are more conservative and stable in the case. .